2009
DOI: 10.1152/ajpcell.00062.2009
|View full text |Cite
|
Sign up to set email alerts
|

Nhe1 is a luminal Na+/H+ exchanger in mouse choroid plexus and is targeted to the basolateral membrane in Ncbe/Nbcn2-null mice

Abstract: The choroid plexus epithelium (CPE) secretes the major fraction of the cerebrospinal fluid (CSF). The Na(+)-HCO(3)(-) transporter Ncbe/Nbcn2 in the basolateral membrane of CPE cells is important for Na(+)-dependent pH(i) increases and probably for CSF secretion. In the current study, the anion transport inhibitor DIDS had no effect on the residual pH(i) recovery in acidified CPE from Ncbe/Nbcn2 knockout mouse by 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein (BCECF)-fluorescence microscopy in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 32 publications
(50 reference statements)
3
85
0
1
Order By: Relevance
“…Future studies are required to determine the exact molecular signaling mechanism(s) involved. Interestingly, a recent study showed that loss of the choroid plexus NCBE transporter resulted in basolateral rather than apical expression of NHE1 (28). This finding as well as the significant changes in the modeling of CPE cells due to loss of NBCe2 complements recent studies that have demonstrated that certain ion transporting proteins have additional important and unexpected roles in generating and maintaining the structural properties of epithelial cells and neurons.…”
Section: Discussionmentioning
confidence: 69%
“…Future studies are required to determine the exact molecular signaling mechanism(s) involved. Interestingly, a recent study showed that loss of the choroid plexus NCBE transporter resulted in basolateral rather than apical expression of NHE1 (28). This finding as well as the significant changes in the modeling of CPE cells due to loss of NBCe2 complements recent studies that have demonstrated that certain ion transporting proteins have additional important and unexpected roles in generating and maintaining the structural properties of epithelial cells and neurons.…”
Section: Discussionmentioning
confidence: 69%
“…The ␤ tot was calculated as the sum of the intrinsic buffering power (␤ int ) and the contribution of the CO 2 /HCO 3 Ϫ buffering system as previously described (10,11) (Fig. 1C) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…That is to say, certain NBCn1-directed polyclonal antibodies suggest a different transporter distribution than others. Some studies report that the localization of NBCn1 in a tissue may vary among species (485) and even among mouse strains (216). Data concerning NBCn1 protein distribution come from the use of the three types of antibodies, those that are generated against: 1) epitopes in the Ct of rat NBCn1 (1014), 2) epitopes in the Ct of human NBCn1 ("anti-NBC3"; Ref.…”
Section: Iv) Other Nbcn1 Variants A) Unusual Variants That Representmentioning
confidence: 99%
“…In light of the prominent role played by NBCn2 in CSF secretion (429), it has been suggested that the role played by NBCn1 in CSF formation may be less significant. Indeed, in some strains of mice, NBCn1 in the CPE is predominantly at the apical membrane (216,470), where the protein would not be in a position to contribute to CSF secretion. Moreover, in NBCn2 and NBCe2 knockout mice, endogenous NBCn1 does not compensate for defective CSF secretion (216,470).…”
Section: I) General A) Ph I Regulation Dids-insensitive (Or Poorlymentioning
confidence: 99%